Synesthesia and Totality in the Theatre of Paul-Napoléon Roinard (1856-1930) (Itinera, 2017)
11th December 1891, at Théâtre d’art, the Cantique des cantiques (“Song of songs”), based on a idea of Paul-Napoléon Roinard went on stage. Roinard used biblical text to create a form of a total theatre, through the stimulation of three of five senses: music and scents try to concrete the poetry of the Chir ha-chirim. Unfortunately Roinard’s career was marked by the folkloric character of this soirée, and most of his dramatic work, as the trilogy Les Miroirs (1908), Le Donneur d’illusions (1920), Les Chercheurs d’impossible (1929), is scarcely known. Yet we find In this trilogy the same synesthetic principles used in the Cantique now included in more impressive epical plays. In this way, Roinard creates a “synthetic theatre”, a bridge between the theatrical aesthetics of Symbolism and that of Simultaneism and Futurism.